Case report: Metastatic refractory undifferentiated small round-cell sarcoma successfully treated with surufatinib and camrelizumab - Li, Yong; Huang, Jinpeng; Chen, Xian; Ye, Yongsong; Du, Xiaohua; Voutsadakis, Ioannis A.; Seetharam, Mahesh; Zhang, Haibo; Lu, Min (Frontiers in Oncology, 2024)
Background: Undifferentiated small round-cell sarcomas (uSRCSs) are a subgroup of sarcomas that are difficult to diagnose. Some uSRCSs have specific gene rearrangements, but others do not. Currently, there is no specific treatments for advanced uSRCSs, and its treatment is largely based on general experience with sarcomas, which A CT scan showed that the tumor achieved a partial response. As of April 2023, the patient had a progression-free survival time of 26 months.Conclusions: Surufatinib in combination with camrelizumab could be effective in the treatment of advanced uSRCSs.